Could green taxation measures help incentivise future Chinese car drivers to purchase low emission vehicles? - Carreno, Michael; Ge, Ying-En; Borthwick, Sarah (Transport, 2014)
The paper begins with a brief review of evidence related to the different types of ‘green’ taxation measures that have been introduced by governments worldwide as a means to lessen the environmental consequences of private car ownership by incentivising the purchase of Low Emission Vehicles (LEV’s). An overview is then provided of current understanding of individuals’ car purchasing decisions, highlighting gaps in knowledge that exist with current explanatory models. Based on these gaps in knowledge and to investigate the potential of various taxation measures in influencing individuals’ car purchasing decisions, an online survey was conducted with students from Dalian University of Technology, China. The questionnaire was designed to measure: (1) situational and psychological factors that would be important for their next car purchase; (2) the impacts of adapting current taxation measures to incentivise LEV purchases; (3) the potential role of a range of taxation measures on their decisions on type of future car purchases. K-Cluster means analysis was employed to identify population segments according to their psychological preparedness and importance attached to situational factors in their future decisions to purchase a LEV, or not. This resulted in three distinct segments – Pro-Greens (33.6% of sample), Maybe-Greens (20.2%) and No-Greens (46.2%). Pro-Greens were more psychologically prepared to purchase LEV’s than the other two segments, whose future car purchasing decisions were primarily driven by situational factors (vehicle characteristics, performance, etc.). Pro-Greens were also more likely to be influenced by changes in current Chinese taxation measures (VAT and fuel duty), and also significantly more likely to be influenced by the introduction of future measures that would incentivise LEV purchases than the other two segments. In terms of future measures to incentivise future Chinese drivers LEV purchases and use, the introduction of a feebate system, a CO2 emissions VAT system, a distance based user charging scheme and annual road tax based on CO2 emissions would appear to have the greatest potential overall. First published online: 09 May 2014